Parametric Study for Vibration Energy Harvester System - M.Z.A, Rahim; M.N.A, Hamid; Z.N.M, Yusuf; S.N.M, Soid (International Journal of Engineering and Technology, 2026)
This paper presented a concept of single degree of freedom (SDOF) electromagnetic vibration energy harvester system with a new technique which introduced two moving mechanical system in a device. New techniques applied in proposed energy harvester system enable to operate at wide bandwidth frequency range, and with two resonances frequency by control the parameter factors. The development of device based on the parameters factor through mathematical modelling. The simulations result based on on the parametric factor shown the proposed mechanical concept in energy harvester system enable to increase bandwidth frequency and vibration transmissibility.
Keywords: Parameter factors; mathematical modelling; vibration energy harvester system